2009
DOI: 10.1021/jm801058n
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Biological Role of the α(2→6)-Linked Sialic Acid in Gangliosides Binding to the Myelin-Associated Glycoprotein (MAG)

Abstract: The tetrasaccharide 1, a substructure of ganglioside GQ1b alpha, shows a remarkable affinity for the myelin-associated glycoprotein (MAG) and was therefore selected as starting point for a lead optimization program. In our search for structurally simplified and pharmacokinetically improved mimics of 1, modifications of the core disaccharide, the alpha(2-->3)- and the alpha(2-->6)-linked sialic acid were synthesized. Biphenylmethyl and (S)-lactate were identified as suitable replacements for the alpha(2-->6)-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 78 publications
0
33
0
Order By: Relevance
“…In addition, the carboxylates of the two Neu5Ac moieties are involved in salt bridges and the C(9)-OH of the α(2-3)-linked Neu5Ac is forming a relevant hydrogen bond. [25] A verification of these findings by docking studies to a homology model of MAG [29,30] revealed the corresponding amino acids forming the binding site (Figs 3 and 6). Based on this information, a rational approach for the design of MAG antagonists was envisaged.…”
Section: Design Of Glycomimeticsmentioning
confidence: 64%
See 4 more Smart Citations
“…In addition, the carboxylates of the two Neu5Ac moieties are involved in salt bridges and the C(9)-OH of the α(2-3)-linked Neu5Ac is forming a relevant hydrogen bond. [25] A verification of these findings by docking studies to a homology model of MAG [29,30] revealed the corresponding amino acids forming the binding site (Figs 3 and 6). Based on this information, a rational approach for the design of MAG antagonists was envisaged.…”
Section: Design Of Glycomimeticsmentioning
confidence: 64%
“…Combined with the most successful modification of the 9-position of the α(2-3)-linked Neu5Ac (Scheme 2) antagonist 29 with low micromolar affinity could be identified (Scheme 4). [30] …”
Section: Lipophilic and Hydrophilic Replacements Of The α(2-6)-linkedmentioning
confidence: 99%
See 3 more Smart Citations